Breeding strategies for genetic improvement - Mwandotto, B.A.J.; Ruvuna, F.; Taylor, J.F.; Cartwright, T.C. (1992)
The SR-CRSP staff at the Ol Magogo Estate is developing a synthetic breed of dual-purpose goat to meet the requirements of small-scale farm families. The objective was to build a goat that has acceptable milk yield, growth rate, fertility, adaptation, and rate of survival under western Kenya conditions. The synthetic dual purpose does were capable of producing 1.1 kg per milking in the day. The toggenbury and Anglo Nubian crossing with that of Galla and East African goats continued in the synthesis of the Dual purpose Goat.